KEDUDUKAN DEBITUR DAN BANK SEBAGAI KREDITUR DALAM HAL WANPRESTASI DEVELOPER (STUDI DI PT. BANK X, CABANG TEBING TINGGI) - HARMONO JAPONIKA (PREMISE LAW JURNAL, 2015)
Credit channeling activities by banks are developing fast. One of the facilities which people are interested in is KPR (Housing Ownership Credit). In the distribution of the facilities of the KPR, sometimes a bank cooperates with a developer to look for a prospective debtor to buy the developer’s houses which have been built or the houses which will be built; or, on the contrary, a developer appoints a certain bank to provide some funds to a debtor who will buy the developer’s houses. The form of cooperation between the bank and the developer is written in a contract. After the prospective debtor is approved to get the credit facilities from the bank, a credit contract commitment and other contract commitments are done. In this case, a debtor buys two houses owned by a developer using KPR facilities of PT. Bank X, but after the credit is liquified by Bank X, the developer fails to build the houses. Keywords: Developer’s Default, Legal Protection for Debtor and Bank, Contract